Possible association between statin use and bowel dysmotility. (28th February 2012) - Fernandes, Roland; Shaikh, Irshad; Wegstapel, Henk
Abstract : 3-Hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitors (statins) are a class of drug that has been proven to be effective in lowering serum lipid levels. Although generally well-tolerated side effects from this class of drug have been noted to include liver dysfunction, renal failure and myopathy. Statins are also known to effect nitric oxide levels through upregulation of nitric oxide synthase. There is some evidence to imply that nitric oxide acts on inhibitory nerves in the colon to produce impaired motility. The authors present a case of recurrent colonic dilatation and volvulus which was initially treated with a sigmoid colectomy. Unfortunately symptoms persisted and a trial of the omission of statins was undertaken resulting in symptomatic relief. Following admission into hospital, statins were inadvertently restarted which caused the symptoms to reoccur. The statin was discontinued and upon review several months later the patient reported symptomatic benefit.